Clcn3 deficiency ameliorates high-fat diet-induced obesity and improves metabolism in mice - Duan, Sirui; Li, Bo; Cui, Shiyu; Chen, Yaoyao; He, Ying; Fan, Lihong (Frontiers in Nutrition, 2024)
Objective: Obesity is defined as excess body fat and is a current health epidemic associated with increased risk for type 2 diabetes and cardiovascular disease. The ClC-3 chloride channel/antiporter, encoded by the Clcn3, is associated with some diseases, like carcinoma, nervous system diseases, and metabolic diseases. To verify the relationship between the Clcn3 and weight including metabolic changes, searching for a new target for metabolic therapy of obesity, we designed the experiment. Methods: The mice were divided into 4 different groups: Clcn3+/+ mice + high-fat diet (HFD), Clcn3-/- mice + HFD, Clcn3+/+ mice + normal diet (ND), Clcn3-/- mice + ND, and fed for 16 weeks. After the glucose tolerance test and insulin tolerance test, peripheral blood and adipose tissues were collected. Moreover, we performed transcriptome sequencing for the epididymal white adipose tissue from Clcn3+/+ and Clcn3-/- mice with the high-fat diet. Western blotting verified the changes in protein levels of relevant metabolic genes. Results: We found that the Clcn3-/- mice had lower body weight and visceral fat, refining glucose and lipid metabolism in HFD-induced mice, but had no effect in normal diet mice. RNA-seq and Western blotting indicated that Clcn3 deficiency may inhibit obesity through the AMPK-UCP1 axis. Conclusion: Modulation of Clcn3 may provide an appealing therapeutic target for obesity and associated metabolic syndrome.